The perception of non-muslim tourists towards halal tourism: a case study in Kuching, Sarawak / Caesar Dealwis ... [et al.] - Dealwis, Caesar; Johari, Aiza; Morni, Affidah (Perpustakaan Tun Abdul Razak UiTM Sarawak, 2022)
Halal tourism is not a topic of discussion among non-Muslim tourists in the city of Kuching, Sarawak when making travel plans, although it is a fast-growing sector in Malaysia. This paper aims to explore the perceptions of non- Muslim tourists in Kuching towards halal tourism. Besides, it also investigates the extent to which non-Muslim tourists in Kuching are willing to purchase halal products and services. Qualitative data were collected by conducting 30 semi- structured interviews with non-Muslim tourists in Kuching. Five major aspects have been identified which describe the perceptions of non-Muslim tourists in the city of Kuching towards halal tourism. This paper also provides some suggestions on how best to attract non-Muslim tourists in Kuching to choose halal tourism. The insight should be of value to the tourism industry in Sarawak.